2020
DOI: 10.1007/s10578-020-01037-x
|View full text |Cite
|
Sign up to set email alerts
|

Initial Challenges of Caregiving During COVID-19: Caregiver Burden, Mental Health, and the Parent–Child Relationship

Abstract: Research confirms that the mental health burdens following community-wide disasters are extensive, with pervasive impacts noted in individuals and families. It is clear that child disaster outcomes are worst among children of highly distressed caregivers, or those caregivers who experience their own negative mental health outcomes from the disaster. The current study used path analysis to examine concurrent patterns of parents' (n = 420) experience from a national sample during the early months of the U.S. COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

60
585
8
28

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 596 publications
(731 citation statements)
references
References 80 publications
(106 reference statements)
60
585
8
28
Order By: Relevance
“…It is important to note, however, that these effects may not be universally experienced by parents. Recent studies have shown that the impact of COVID-19 among parents varies with caregiver burden, perceptions of children's stress (Russell et al, 2020), and the availability of resources to meet caregiver needs (Griffith, 2020). Therefore, while this study shows that young children, on average, are associated with reduced mental distress among parents, there are likely nuances in the experience of mental distress among parents as a result of these factors and other characteristics of family and work structure (e.g., age of children, fleixibility of job, support system).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note, however, that these effects may not be universally experienced by parents. Recent studies have shown that the impact of COVID-19 among parents varies with caregiver burden, perceptions of children's stress (Russell et al, 2020), and the availability of resources to meet caregiver needs (Griffith, 2020). Therefore, while this study shows that young children, on average, are associated with reduced mental distress among parents, there are likely nuances in the experience of mental distress among parents as a result of these factors and other characteristics of family and work structure (e.g., age of children, fleixibility of job, support system).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of COVID-19 in the United States has created unprecedented challenges that have rendered many individuals financially unstable (Goodell, 2020) and emotionally vulnerable (Li et al, 2020). The well-being of families may be particularly at risk as a result of changes in relationships and routines during COVID-19, which may disproportionately affect children's coping abilities and parental burden (Prime, Wade, & Browne, 2020;Russell, Hutchison, Tambling, Tomkunas, & Horton, 2020). Although emerging evidence suggests that there has been a rise in mental distress throughout the pandemic (Kirzinger, Kearney, Hamel, & Brodie, 2020), there is not, to our knowledge, any existing research on the association between household structure and mental distress.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, working mothers are frequently frustrated in balancing two seemingly contradictory tasks of childbearing and career, resulting in psychological disorders and physical illnesses, as well as producing disruptive behaviors in children [24]. Such stress becomes intensified under the high level of uncertainty and subsequent perceived risks such as COVID-19 [25][26][27].…”
Section: Parental Stress and Social Supportmentioning
confidence: 99%
“…During the pandemic, parents spent more time with their children in different types of activities, including playing more games, watching more television, and playing with more toys (Lee et al, 2020). Because of the added stressors of parenting during a pandemic, caregivers of children were at an increased risk of experiencing adverse mental health symptoms compared to non-parents (Russell et al, 2020). Parents' reports of daily mood were significantly more negative during the pandemic than before its onset (Gassman-Pines et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Parents' reports of daily mood were significantly more negative during the pandemic than before its onset (Gassman-Pines et al, 2020). Furthermore, the additional parenting needs and increased stressors were contributors to compromised parent-child relationships (Russell et al, 2020). In a national survey study assessing the physical and emotional well-being of parents and children in the United States in June 2020, there were significant links between parents' mental health, children's stress, and parent-child closeness and conflict (Russell et al, 2020).…”
Section: Introductionmentioning
confidence: 99%